Save the reindeer! - Thyne, Tone.; Nee, Chris; Scanlon, Michael; Little Airplane Productions; Nick Jr. (Firm) (London : Simon and Schuster/Nick Jr., 2009)
The Wonder Pets travel to the North Pole to rescue a lost reindeer.
"Nick Jr.".
Based on the TV series Wonder Pets! as seen on Nick Jr.
1.7
K-3
Keywords: Christmas stories; Helping behavior -- Juvenile fiction; Pets -- Juvenile fiction; Reindeer -- Juvenile fiction; Christmas -- Fiction; Helpfulness -- Fiction; Pets -- Fiction; Reindeer -- Fiction; Stories in rhyme; Christmas -- Fiction; Helping behavior -- Fiction; Pets -- Fiction; Reindeer -- Fiction; Stories in rhyme